Implementation of Safety Talk on Construction Project At PT Kerinci Meragin Hidro Batang Merangin Kerinci District In 2023 - Larasati, Adisti Qamahadlina; Yosalli (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
The promotion of Occupational Health and Safety (OHS) through the safety talk program aims to convey the message of occupational health and safety in the workplace. As written in PP No. 50 of 2012 related to the implementation of SMK3, OHS communication through the safety talk program is one of the supporting components of work accident prevention efforts. The purpose of this study is to observe the implementation of safety talk on safety behavior in the Kerinci Merangin Hidro hydropower development project. The research was conducted qualitatively at PT Kerinci Merangin Hidro Batang Merangin, Kerinci Regency, in February-June 2023, using 7 research informants consisting of 1 HSE person, 1 HSE officer, and 5 workers. Data collection is carried out by interviews and observations, and processing of interview results is carried out by making data transcripts, reducing data, and drawing conclusions. The results of this research show that safety talk activities at PT Kerinci Merangin Hidro have been implemented well with the implementation of safety talks carried out by a team from the HSE division directly. With a safety talk method that is easy to understand and interesting for workers. Advice for the HSE division team of PT Kerinci Merangin Hidro to always adjust the material to be delivered during the implementation of safety talk in accordance with the conditions that occur in the field.